Rethinking Production. A Step Beyond the Hylomorphic and Anthropocentric Approach - JAKUBOWSKI, Dimitri Jan (Studia Universitatis Babeș-Bolyai Philosophia, 2024)
This research examines three thematic areas: philosophy, education, and ecology. It aims to be an interdisciplinary study, fundamentally based on the importance of the philosophy of environmental education and the practical implications that it can have. The problem of the contemporary hylomorphic production approach is first examined and then educational solutions are outlined towards a holistic understanding of the environment and of producing with it and not on it. By environment, in research, we also mean the human being because this is only one of his many appendages; therefore, as such, we try to relocate him to a non-privileged place (a place where he has been autonomously placed for centuries). It aims to be a militant study towards a different anti-anthropocene educational approach that finds its paradigm in the “Green Schools” of Bali, as we will see in the conclusion.